2015
DOI: 10.1111/jth.12893
|View full text |Cite
|
Sign up to set email alerts
|

Platelet and endothelial cell P-selectin are required for host defense against Klebsiella pneumoniae-induced pneumosepsis

Abstract: To cite this article: de Stoppelaar SF, van't Veer C, Roelofs JJTH, Claushuis TAM, de Boer OJ, Tanck MWT, Hoogendijk AJ, van der Poll T.Platelet and endothelial cell P-selectin are required for host defense against Klebsiella pneumoniae-induced pneumosepsis. J Thromb Haemost 2015; 13: 1128-38.Summary. Background: Sepsis is associated with activation of platelets and endothelial cells accompanied by enhanced P-selectin surface expression. Both platelet-and endothelial P-selectin have been associated with leukoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 41 publications
1
40
1
1
Order By: Relevance
“…This model is associated with a gradually growing bacterial load in the lungs with subsequent dissemination to distant body sites and organ injury, allowing studies on the role of components of innate immunity in early host defense as well as tissue damage during late-stage infection. We demonstrated that the number of platelets is a major denominator of their role in pneumosepsis [19], and identified platelet P-selectin [11] and GPVI [12] as mediators contributing to the control of bacterial growth. The current study suggests that platelet δ granules may contribute to thrombocytopenia in severe infection and can most likely thereby impair antibacterial defense during pneumonia-derived sepsis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This model is associated with a gradually growing bacterial load in the lungs with subsequent dissemination to distant body sites and organ injury, allowing studies on the role of components of innate immunity in early host defense as well as tissue damage during late-stage infection. We demonstrated that the number of platelets is a major denominator of their role in pneumosepsis [19], and identified platelet P-selectin [11] and GPVI [12] as mediators contributing to the control of bacterial growth. The current study suggests that platelet δ granules may contribute to thrombocytopenia in severe infection and can most likely thereby impair antibacterial defense during pneumonia-derived sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…We previously used this model of pneumonia-derived sepsis caused by the common human pathogen K. pneumoniae to study the role of platelets and platelet receptors in the host response to severe infection [11, 12, 19, 37]. This model is associated with a gradually growing bacterial load in the lungs with subsequent dissemination to distant body sites and organ injury, allowing studies on the role of components of innate immunity in early host defense as well as tissue damage during late-stage infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, thrombocytopenia increases bacterial burden in some inflammatory settings, such as Streptococcus pneumoniae -induced pneumonia while not affecting neutrophil infiltration (129). Furthermore, P-selectin-deficiency results in reduced circulating PMAs during Klebsiella pneumoniae -induced pneumonia, but has no effect on pulmonary leukocyte sequestration (130). However, thrombin inhibition reduces PNA formation in vitro and exacerbates sepsis in K. pnemoniae -induced pneumosepsis, but fails to reduce neutrophil recruitment or NET formation in vivo (131).…”
Section: Platelet-leukocyte Interactions In Pathologic Conditionsmentioning
confidence: 99%
“…45,46 Specifically, the involvement of platelet P2Y 12 in sepsis has been suggested on the grounds of the inhibitory effect of the P2Y 12 antagonist ticagrelor on platelet-neutrophil aggregate formation, neutrophil recruitment, and lung damage in mice subjected to cecal ligation and puncture. 47 However, because ticagrelor also inhibits adenosine uptake, the possibility that its protective effect might be related at least partially to its effect on adenosine metabolism cannot be ruled out.…”
Section: 41mentioning
confidence: 99%